Comparison of serum electrolytes with preeclampsia severity: a cross sectional study - Khan, Javid Ahmed; Ashraf, Aadil; Qureshi, Waseem A.; Fayaz, Faizana (International Journal of Research in Medical Sciences, 2022)
Background: Preeclampsia is a common complication of pregnancy that put women and their fetuses at significant risk and result in life long sequelae. The pathogenesis of this important disease is complex as such the role of different serum electrolytes is being investigated as they are considered important for blood pressure regulation. Methods: A hospital based cross-sectional study of 100 diagnosed cases of preeclampsia divided into mild and severe according to latest International Society for the Study of Hypertension in Pregnancy (ISSHP) guidelines and equal number of age, parity and gestational age matched women (n=100), that acted as control group, with singleton normal pregnancies. Data was analyzed in SPSS V:26. Statistical tests to find out mean standard deviation and One-way ANOVA test were applied to find the significance of associations. Results: In severe preeclampsia group, the mean values of Na+, K+ and Cl- were 134.50±4.24, 4.28±0.74, 106.48±3.41 meq/l respectively in comparison to control group which had 135.57±3.29, 4.12±0.53, 108.20±3.19 meq/l respectively. Results from one way ANOVA showed that there was statistically significant difference between means of the three groups for systolic blood pressure (SBP), diastolic blood pressure (DBP), potassium and chloride levels with p<0.05. A post hoc analysis was used to distinguish the differences in means of these parameters. Conclusions: Estimation of readily available serum electrolytes of sodium potassium and chloride during the course of pregnancy can help to identify and treat preeclampsia and thus reduce the burden of morbidity and mortality in pregnant women.